Frontier Exploration Using an Integrated Approach of Seafloor Multibeam, Drop Core and Seismic Interpretation – A Study Case from North Banggai Sula - Farid Ferdian (Ikatan Ahli Geologi Indonesia, 2015)
Exploration in frontier areas is always challenging and has resulted in the development of various new technologies including georeferenced, high resolution seafloor multibeam bathymetry and backscatter. The multibeam bathymetry data provides sea floor depth information, while the backscatter data records the amount of acoustic energy received by the sonar after interactions with the sea floor and are used to infer seabed features and materials. Interpretation of these new dataset combined with piston cores and seismic data have been conducted in the offshore of North Banggai Sula. This integrated approach has been termed as SeaSeepTM technology.